524 NAPS. (3rd May 2021) - Elliott, Jonathan; Lim, Miranda; Keil, Allison; Avidan, Alon; Bliwise, Donald; Gagnon, Jean-Francois; Howell, Michael; Huddleston, Daniel; McCleland, Jennifer; St. Louis, Erik; Postuma, Ronald; Videnovic, Aleksandar; et al.
Abstract: Introduction: Rapid Eye Movement (REM) Sleep Behavior Disorder (RBD) is characterized by a lack of muscle atonia during REM sleep with dream enactment. RBD is regarded as a prodromal synucleinopathy as a high proportion of patients eventually phenoconvert to Parkinson's Disease and related synucleinopathies, suggesting RBD may be an early non-motor symptom of disease. Accordingly, patients with RBD are ideally situated to test potential therapeutic interventions to prevent phenoconversion to synucleinopathy. However, RBD itself, and associated patient registries, are rare. The North American Prodromal Synucleinopathy Consortium (formed in 2018) establishes a multisite registry of RBD patients with standardized neurological, neuropsychiatric, and neuropsychological assessments and biomarker collection. The present work reports baseline characteristics of this RBD patient database at its current state. Methods: Seven participating sites have contributed n=170 polysomnographically-confirmed RBD patients. Data includes past medical and family history, self-report questionnaires, and neuropsychological, motor, sensory, and autonomic function testing. Additionally, all subjects have contributed blood, and a subset of subjects have contributed cerebrospinal fluid samples to the National Centralized Repository for Alzheimer's Disease and Related Dementias for future analysis. A final diagnosis for each subject was determined through an adjudication process by NAPS Consortium PIs; subjects were categorized as ether: 1) isolated RBD, 2) RBD+, 3) Early Symptomatic, or 4) Phenoconverted. Results: Of the n=170 subjects, there were n=39 isolated RBD, n=81 RBD+, n=45 Early Symptomatic, and n=4 Phenoconverted. Isolated RBD subjects have no other early neurodegeneration signs/symptoms, those with RBD+ have at least one other identifiable early/mild symptom. The early symptomatic group includes those with mild or subjective cognitive impairment, pure autonomic failure, or possible multiple systems atrophy. The Phenoconverted group consists of those with Dementia with Lew Bodies, Dementia NOS, Parkinson's Disease, or Parkinson's NOS. The distribution of impairment across the 5 major domains (motor, cognitive, autonomic, sensory, and psychiatric) for each of the 4 groups will be described. Conclusion: This interim analysis presents data on n=170 subjects. The target enrollment is n=360 across the 7 original sites plus 3 new sites. Future work will follow these subjects longitudinally to assess rates and predictors of phenoconversion. Support (if any): NIH NIA R34 AG056639 (YJ, BB)